Fairness and microcredit interest rates: from Rawlsian principles of justice to the distribution of the bargaining range. (13th May 2013) - Hudon, Marek; Ashta, Arvind
<x xml:space="preserve">Abstract</x> This paper addresses the fairness of microcredit interest rates. Since microfinance institutions provide credit for the poor at relatively high prices, the fairness of their interest rates has been repeatedly debated. We first apply Rawls' principles of justice to the case of microcredit interest rates and suggest some limitations related to the hypothesis of rationality of the borrowers and the level of inequality. We then suggest another framework based on the analysis of the distribution of the benefits generated by the transaction to assess the fairness of interest rates. We conceptualize this as the distribution of the bargaining range between the borrowers' and the institutions' reservation price and discuss what these reservation prices could be in the context of microfinance.